The Effects of Mindfulness-Based Interventions on Mental Health, Quality of Life, and Physical Activity in Cancer Patients: A Literature Review - Pazio, Klaudia; Michał Piskor; Strzalińska, Dominika; Choroszewska, Ewelina; Bajko, Julia; Chmielewski, Michał; Bullmann, Agnieszka; Kapusta, Kinga; Ciszewski, Artur; Błażewicz, Juliusz (Quality in Sport, 2026)
Cancer is a major burden in both the somatic and psychological dimensions. Oncology patients often experience high levels of stress, anxiety, depression, and reduced quality of life resulting from both the diagnosis itself and the course of treatment. In recent years, growing attention has been paid to psychosocial interventions that help patients cope with these difficulties. One such approach is mindfulness-based interventions (MBIs), including programs such as Mindfulness-Based Stress Reduction (MBSR). The aim of this paper was to review the literature on the impact of mindfulness-based interventions on mental health, quality of life, and physical activity among cancer patients.